Hambatan Eksekusi Putusan PHI terhadap Perkara Pemutusan Hubungan Kerja Gorontalo - Gobel, Alyah Putri Arneta (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the obstacles to executing decisions of the Industrial Relations Court (PHI) in employment termination (PHK) cases at the Gorontalo District Court and to formulate strategies for improving the effectiveness of their enforcement. The findings show that although PHI decisions have permanent legal force, their implementation often encounters barriers, preventing workers’ rights from being fulfilled optimally. This research applies an empirical legal method with a juridical-sociological approach, combining a normative review of statutory provisions such as Law Number 2 of 2004, Law Number 13 of 2003, and the provisions of the Herziene Indonesisch Reglement (HIR)/Reglement Buitengewesten (RBg) with factual findings based on data from the Case Tracking Information System (SIPP) and interviews with relevant stakeholders. The results indicate that the main obstacles include employers’ non-compliance with court rulings, the limited availability of assets for seizure, the inherent difficulty in enforcing constitutive decisions, the insufficient number and competence of bailiffs, lengthy administrative procedures, and high execution costs. Empirical data from 2020–2024 show varying execution success rates, although a gradual improvement trend is observed. Strategic recommendations include drafting specific execution regulations for industrial relations cases, strengthening the capacity of court officers particularly bailiffs, imposing strict sanctions on violators, utilizing information technology for transparency and acceleration of the process, and fostering multi-stakeholder collaboration between the government, trade unions, employers, and civil society. This study underscores the urgency of comprehensive reform to ensure that the protection of workers’ rights is not merely normative but is substantively realized, thereby reinforcing the rule of law in the labor sector and enhancing public trust in the industrial relations judicial system.